Central banks' supervisory guidance on corporate governance and bank stability: Evidence from African countries - Samuel Mutarindwa; Dorothea Schäfer; Andreas Stephan (Emerging Markets Review, 2020)
This paper focuses on the identification of the causal relationship between central banks' supervisory guidance and individual bank stability. We propose and test the hypothesis that this causal relationship is mediated by the degree to which banks comply with their central bank's corporate governance recommendations. Specifically, we exploit the fact that there is considerable cross-country heterogeneity in providing supervisory guidance. Our recursive two-equation system is equivalent to an endogenous treatment effect model in which the treatment is the provision of supervisory guidance. We find that institutional factors, in particular the legal family of origin, political stability, contract enforcement and strength of investor protection promote provision of supervisory guidance. If a central bank has published supervisory guidance, local banks show better internal governance and higher stability.
Keywords: G21; G28; G30; G32; G38; 330; African banks; Central bank; Supervisory guidance; Corporate governance; Legal systems; Institutions; Bank stability